ANALISIS EFISIENSI TEKNIS USAHA TANI CABAI MERAH KERITING DI KABUPATEN TANAH DATAR - Chaniago, Putra; Syahni, Rahmat; Hafizah, Dian (Fakultas Pertanian Universitas Janabadra, 2025)
The productivity of Curly Red Chillies in Tanah Datar Regency is lower than the average in West Sumatra. The objectives of this study are to: (1) analyse the factors affecting the productivity of red chilli in Tanah Datar Regency, (2) analyse the level of technical efficiency of red chilli in Tanah Datar Regency, (3) analyse the factors affecting the technical efficiency of red chilli in Tanah Datar Regency. The method used in this research is the survey method on 80 samples through random sampling. Data analysis using Cobb-Douglas stochastic frontier production function. The results showed that the factors that have a positive and significant effect on the productivity of kerinting red chillies are seeds, manure, ZA fertiliser, and labour. While the factors that have a negative and significant effect are kcl fertiliser, npk phonska fertiliser, and zpt. This explains that any addition of factors that have a positive and significant effect will increase production and vice versa, any addition of factors that have a negative and significant effect will reduce the production of curly red chilli. Therefore, it is necessary to increase the productivity factors of seeds, manure, ZA fertiliser, and labour and reduce the inputs of kcl fertiliser, npk phonska fertiliser and ZPT for more efficient curly red chilli farming.